Effects of Dimethyl Fumarate on Brain Atrophy in Relapsing-Remitting Multiple Sclerosis: Pooled Analysis Phase 3 DEFINE and CONFIRM Studies - Nakamura, Kunio; Mokliatchouk, Oksana; Arnold, Douglas L.; Yousry, Tarek A.; Kappos, Ludwig; Richert, Nancy; Ayling-Rouse, Katherine; Miller, Catherine; Fisher, Elizabeth (Frontiers in Neurology, 2022)
Objective: In the pivotal DEFINE and CONFIRM trials for dimethyl fumarate (DMF), patterns of brain volume changes were different, potentially due to low sample sizes and because MRIs were analyzed at two different reading centers. We evaluated effects of DMF on brain volume change in patients with multiple sclerosis (MS) through reanalysis of pooled images from DEFINE/CONFIRM trials in one reading center. Methods: MRIs from DEFINE/CONFIRM at weeks 0, 24, 48, and 96 from patients randomized to twice-daily DMF or placebo (PBO) were reanalyzed at the Cleveland Clinic to measure brain parenchymal fraction (BPF). To account for pseudoatrophy, brain volume estimates were re-baselined to calculate changes for weeks 48‒96. Results: Across studies, 301 and 314 patients receiving DMF and PBO, respectively, had analyzable MRIs. In weeks 0‒48, mean ± SE percentage change in BPF was ‒0.44±0.04 versus ‒0.34±0.04% in DMF versus PBO, respectively, whereas in weeks 48‒96, mean±SE percentage change in BPF was ‒0.27±0.03 versus ‒0.41±0.04% in DMF versus PBO, respectively. The mixed-effect model for repeated measures showed similar results: in weeks 48‒96, estimated change (95% confidence interval) in BPF was ‒0.0021 (‒0.0027, ‒0.0016) for DMF versus ‒0.0033 (‒0.0039, ‒0.0028) for PBO (35.9% reduction; p = 0.0025). Conclusions: The lower rate of whole brain volume loss with DMF in this pooled BPF analysis in the second year versus PBO is consistent with its effects on relapses, disability, and MRI lesions. Brain volume changes in the first year may be explained by pseudoatrophy effects also described in other MS clinical trials.